DEVELOPING ANIMATION VIDEO FOR TEACHING NARRATIVE TEXT TO EIGHTH GRADE STUDENTS OF SMP NEGERI 2 LUBUK PAKAM - Yunikartika Damanik; Muhammad Eko Isdianto (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2022)
The aim of this study was to developed animation video as media in teaching writing narrative text for the eighth grade students of SMP Negeri 2 Lubuk Pakam. Due to the result in the form of product, this study was categorized as Research and Development (R & D) study which adapted from Borg and Gall (2003) theory with some modifications. The subject of the study was the eighth grade students of SMP Negeri 2 Lubuk Pakam. In conducting this study, the procedured were gathering the data and information, conducting the need analysis designing the first draft of media, revising the media and producing the final product as the animation video. The instruments of collecting the data were the combination of two strategies; interview and questionnaires. The data were gathered by administering interview to English teacher and distributing questionnaires to 30 respondents to get the students’ needs. The interview and questionnaires result prove that the students need animation video as a media in teaching writing which can help the students to understand about the narrative text. The new animation video consists of some pictures, characters and explanations that can be used in teaching writing narrative text. The media had been validated by two validators. The first validator gave 89.6% and the second validator gave 95.2% that it could be inferred that the developed media was appropriate to be used for students. The result of the study was the animation video that the teacher can use as the teaching media of narrative text for the eighth grade students of SMP Negeri 2 Lubuk Pakam.